PENGENDALIAN PERSEDIAAN BAHAN BAKU TERHADAP PROSES PRODUKSI (Studi kasus di PERUSAHAAN SURABAYA) - daengs, achmad; aripin, samsul (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2018)
ABSTRAKThe companies that produce donut & coffee with a brand that has been known almost throughout the territory of Indonesia called Mokko Factory Donut & Coffee.some problems are often encountered about raw material inventory in PT.Talenta Packaging Industry, including stock materials in the warehouse do not always meet all well according to the estimate already set. The conclusion of this research is the result of raw material control calculation using Economic Order Quantity at PT. Talenta Packaging Industries in Surabaya in 2015 amounted to 1288.97 kg while in the Year 2016 of 1,507.73 kg. The results of the calculation of raw material control using Safety Stock 2015 amounted to 153.29 kg. While the results of the calculation of raw material control using Safety Stock in the Year 2016 of 111.05 kg. The result of raw material control calculation using Re Order Point in 2015 amounted to 209,41kg. While the year 2016 amounted to 246.78 kg. There are savings on the control of raw materials inventory according to the calculation using the method of controlling raw materials by the method of calculation of PT. Talenta Packaging This industry is shown by total inventory cost in 2015 according to PT. Talenta Packaging Industry amounting to Rp 1,399,338.14 while according to EOQ Rp. 796.420,861. Thus, in 2015 there is a total cost savings of inventory amounting to Rp 466,332,879. While in the year 2016 total inventory cost according to PT. Talenta Packaging Industry amounted to Rp1,489,153.04 while according to EOQ Rp 945.305,093. So there is a total cost savings of inventory amounting to Rp 543,847.947. Â Keywords: Control of raw material inventory Economic Order Quantity, Safety Stock, Re Order Point, Total Inventory Cost, Maximum Inventory